2015
DOI: 10.1590/1678-457x.6552
|View full text |Cite
|
Sign up to set email alerts
|

Sensory descriptors of cocoa beans from cultivated trees of Soconusco, Chiapas, Mexico

Abstract: The odor and taste profile of cocoa bean samples obtained from trees cultivated in southern Mexico were evaluated by trained panelists. Seven representative samples (groups) of a total of 45 were analyzed. Four attributes of taste (sweetness, bitterness, acidity and astringency), and nine of odor (chocolate, nutty, hazelnut, sweet, acidity, roasted, spicy, musty and off-odor) were evaluated. A sample (G7) with higher scores in sweet taste and sweet and nutty odors was detected, as well as a high association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Before the evaluation, 100 g of raw beans from each representative group of the Amazonian, Andean and coastal regions was cleaned, the rind was removed, and the beans were ground into small pieces. A total of 30 sealed plastic containers were prepared for taste and aroma, each one with a content of 1.5 g of ground beans, modified from [ 65 ]. The containers were sealed and left for 6 h at a temperature of 28 °C to promote the accumulation of volatiles.…”
Section: Methodsmentioning
confidence: 99%
“…Before the evaluation, 100 g of raw beans from each representative group of the Amazonian, Andean and coastal regions was cleaned, the rind was removed, and the beans were ground into small pieces. A total of 30 sealed plastic containers were prepared for taste and aroma, each one with a content of 1.5 g of ground beans, modified from [ 65 ]. The containers were sealed and left for 6 h at a temperature of 28 °C to promote the accumulation of volatiles.…”
Section: Methodsmentioning
confidence: 99%
“…However, volatiles with potentially undesirable rancid, waxy, or sulfurous aroma including propanoic acid, cyclohexanol, and thiobis-methane, as well as compounds with no database aroma records such as 1-amino-1-ortho-chlorophenyl-2-(2-quinoxaliny)ethene, and undecylamine were among the main compounds in Criollo cacao after a 3-day fermentation period. Normal presence of waxy, rancid, and sulfurous aroma compounds has been reported in cocoa samples from various origins [30] and has been related to inappropriate posthandling of the pods [31] but the reported overall effect of undesirable compounds on sensory scores of fermented Criollo cacao has been low [29]. Similarly, Nacional cacao showed predominant amounts of volatiles with fruity, green, and woody aromas at the end of the fermentation (3 days), including 2-nonanone, 3-octen-1-ol, 2-octanol acetate, 2-undecanone, valencene, and aromadendrene.…”
Section: Analysis Of Volatile Profilementioning
confidence: 99%
“…Vázquez‐Ovando et al . (2015) found that the scores were higher for the sour taste than for the bitter taste for cocoa beans from the Sonosco cultivar (Chiapas, Mexico). The authors reported that cocoa from different regions of the world present different contents of organic acids, monosaccharides, disaccharides, oligosaccharides, and some L‐amino acids, depending on the latitude and climate, which have a determining impact on attributes as sourness and sweetness.…”
Section: Resultsmentioning
confidence: 99%